PECULIARITIES AND ADVANTAGES OF APPLICATION OF MODERN PLAST-POLYMER MATERIALS FOR PATTERN EQUIPMENT PRODUCTION - I. A. Nelub; P. A. Kushel; S. L. Rovin (Литьë и металлургия)
The peculiarities and advantages of application of the modern plast-polymeric materials for production of pattern equipment are examined